Evaluation of efficiency of chemical fuel burning - Козлов, В. В. (Proceedings of National Aviation University (archive), 1998)
Considered is the evaluation of effectiveness of chemical fuel combustion using relative increase of combustion efficiency as criterion of efficiency of chemical fuel burning. The combustion efficiency is determined by increase of gas temperature for burning standard and treated fuel in two geometrical similar combustion chambers under equal conditions